KAJIAN METODE PERSALINAN NORMAL DENGAN BANTUAN CERMIN PADA PERSALINAN KALA II IBU PRIMIGRAVIDA - Rokhamah, Rokhamah; Qotimah, Qotimah (Care : Jurnal Ilmiah Ilmu Kesehatan, 2019)
The success of labor is influenced by several factors, namely maternal factors (power, passage, psychology), fetal factors (placenta) and helping factors. Using mirror aids in the process of progress in labor at a second time can increase maternal motivation psychologically and emotionally, this preventing and or decreasing pathological labor prevalence. The purpose of this study was determining the difference in time in mothers who had labor in the second time using a mirror and who did not use a mirror. The design of this study used True - experiment with post test only Control design, the sample of study were 40 physiologically 20 primigraphic delivery mothers who were treated, 20 were not treated and taken randomly. The purpose of this study was determining the time difference in labor mothers when second uses a mirror and does not use a mirror. Observation data collection techniques, it used unpaired T test. This research was conducted in 2018 in the Poncokusumo Malang Health Center. The results showed that labor with the help of a mirror could accelerate the second stage of labor in primigravida mothers. This is evidenced by the average time used by maternity in group I (using mirrors) is 7.05 minutes and the average time used by group II maternity women (without using a mirror) is 16.15 minute . The use of a mirror aid can be used as an instrument complement labor in order to reduce maternal morbidity and mortality in Indonesia.